2013
DOI: 10.4314/jab.v65i0.89642
|View full text |Cite
|
Sign up to set email alerts
|

Impact of osmotic dehydration on the encapsulated apices survival of two yams (<i>Dioscorea</i> spp.) genotypes from Benin

Abstract: Objective: Cryopreservation is one of the biotechnological methods currently used for long term conservation of plant genetic resources. It requires many steps such as a pretreatment, which involves cells dehydration in order to make them tolerant to desiccation and freezing in nitrogen liquid using high sucrose concentration. The present study aims to establish a protocol for long term conservation of yam germplasm in Benin using encapsulation/dehydration technique. Methodology and Results: The effects of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…However, in Dioscorea spp. shoot apices, a higher survival and regeneration rates were reported after applying 24-h dehydration, as compared to longer (40-h) treatment [Agbidinoukoun et al 2013]. In the present study a short (4-day) osmotic dehydration proved more optimal in terms of explants survival, their regrowth potential and the quality of the microshoots produced than that 7-day-long one, which is in conjunction with a poor response of the explants to higher sucrose concentrations during preculture.…”
Section: Role Of Preculture In Cryopreservation Of Plant Materialssupporting
confidence: 40%
“…However, in Dioscorea spp. shoot apices, a higher survival and regeneration rates were reported after applying 24-h dehydration, as compared to longer (40-h) treatment [Agbidinoukoun et al 2013]. In the present study a short (4-day) osmotic dehydration proved more optimal in terms of explants survival, their regrowth potential and the quality of the microshoots produced than that 7-day-long one, which is in conjunction with a poor response of the explants to higher sucrose concentrations during preculture.…”
Section: Role Of Preculture In Cryopreservation Of Plant Materialssupporting
confidence: 40%
“…As for Gladiolus, shoots from two in vitro-grown cultivars were sensitive to KIN resulting in a high rate (20-80%) of abnormal-looking regenerants (Joung et al 2007). According to Agbidinoukoun et al (2013), the callus induction mechanism is still poorly understood and depends mostly on genotype, which could explain the differences between cultivars observed in this study.…”
Section: Cryopreservation Efficiencymentioning
confidence: 93%
“…Despite in-situ conservation is preferentially applied for genetic resources for several woody species and cultivated species, ex-situ conservation remain the challenge for maintenance of the non-orthodox and vegetative propagated species (Engelmann, 2010). Since, several studies reported that cells and organs in vitro culture techniques are successfully used for conservation of yam germplasm (Engelmann, 1991;Ahanhanzo et al, 2003;Mandal and Sonali, 2007;Agbidinoukoun et al, 2013). Those techniques offer more advantages such as rapid multiplication of explants, require lower area, free diseases plantlets production.…”
Section: Introductionmentioning
confidence: 99%